Abuses in virtual space and aiding suicide - Szabó, Barbara (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Cyberbullying abuses in virtual space can also qualify as stalking in a criminal law obscurity, my thesis notes that the concept of harassment is examined from as many aspects as possible. It raises awareness of the current icings of the harassment, and to provide a summary of the subject that can be used in the older ones for the mouths of the livers.